Doxycycline Modulates Smooth Muscle Cell Growth, Migration, and Matrix Remodeling after Arterial Injury - Bendeck, Michelle P. (American Society for Investigative Pathology, 2002)
The tetracyclines function as antibiotics by inhibiting bacterial protein synthesis, but recent work has shown that they are pluripotent drugs that affect many mammalian cell functions including proliferation, migration, apoptosis, and matrix remodeling. Because all of these processes have been implicated in arterial intimal lesion development, the objective of these studies was to examine the effect of doxycycline treatment using a well-characterized model of neointimal thickening, balloon catheter denudation of the rat carotid artery. Rats were treated with 30-mg/kg/day doxycycline. Doxycycline reduced the activity of matrix metalloproteinase (MMP)-2 and MMP-9 in the arterial wall, and inhibited smooth muscle cell migration from media to intima by 77% at 4 days after balloon injury. Replication of smooth muscle cells in the intima at 7 days was reduced from 28.3 ± 2.5% in controls to 17.0 ± 2.8% in doxycycline-treated rats. The synthesis of elastin and collagen was not affected, but accumulation of elastin was blocked in the doxycycline-treated rats. By contrast, collagen accumulation was not affected, which led to the formation of a more collagen-rich intima. At 28 days after injury, the intimal:medial ratio was significantly reduced from 1.67 ± 0.09 in control rats to 1.36 ± 0.06 in the doxycycline-treated rats. This study shows that doxycycline is an effective inhibitor of cell proliferation, migration, and MMP activity in vivo. Further study in more complicated models of atherosclerosis and restenosis iswarranted.